2008
DOI: 10.1111/j.1399-3054.2008.01168.x
|View full text |Cite
|
Sign up to set email alerts
|

Relative contribution of AtHAK5 and AtAKT1 to K+ uptake in the high‐affinity range of concentrations

Abstract: The relative contribution of the high-affinity K(+) transporter AtHAK5 and the inward rectifier K(+) channel AtAKT1 to K(+) uptake in the high-affinity range of concentrations was studied in Arabidopsis thaliana ecotype Columbia (Col-0). The results obtained with wild-type lines, with T-DNA insertion in both genes and specific uptake inhibitors, show that AtHAK5 and AtAKT1 mediate the NH4+-sensitive and the Ba(2+)-sensitive components of uptake, respectively, and that they are the two major contributors to upt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
176
1
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(188 citation statements)
references
References 40 publications
6
176
1
5
Order By: Relevance
“…By contrast, induction of second-order LRs by low-K was significantly weaker in mutant plants defective for the K-channel AKT1 (akt1). This finding is surprising since AKT1 is not required for K-nutrition in low-K as long as HAK5 is functional (Rubio et al, 2008). Nevertheless, a role of AKT1 was further supported by the observation that induction of second-order LRs by low-K was completely abolished in mutant plants defective for the The effects of individual and double nutrient starvation on RSA, visualized as radar charts.…”
Section: Two Distinct K/n Signaling Modules Regulate Lr Branching Andmentioning
confidence: 76%
See 1 more Smart Citation
“…By contrast, induction of second-order LRs by low-K was significantly weaker in mutant plants defective for the K-channel AKT1 (akt1). This finding is surprising since AKT1 is not required for K-nutrition in low-K as long as HAK5 is functional (Rubio et al, 2008). Nevertheless, a role of AKT1 was further supported by the observation that induction of second-order LRs by low-K was completely abolished in mutant plants defective for the The effects of individual and double nutrient starvation on RSA, visualized as radar charts.…”
Section: Two Distinct K/n Signaling Modules Regulate Lr Branching Andmentioning
confidence: 76%
“…The physiological relevance of this pathway, however, has remained a mystery because AKT1 does not make a major contribution to K-uptake in low-K conditions as long as HAK5 is active (Rubio et al, 2008). Our study not only identified LR branching as a developmental, target process of this signaling module ( Figures 7A and 1B), but also linked it with the nitrate-transceptor NRT1.1, another target of CIPK23 (Ho et al, 2009).…”
Section: Cipk23mentioning
confidence: 87%
“…The elevated suberin in tsc10a may also be responsible for the enhanced Na, K, and Rb observed in the mutant, since similar changes were also observed in the esb1 mutant (Baxter et al, 2009). One possible mechanism to explain the elevated leaf Na and K may be that increased resistance to Na + and K + transport via the apoplastic pathway increases the movement of these ions via a more efficient symplastic transport pathway mediated by high affinity transporters, such as the Na transporter HKT1 (Uozumi et al, 2000) and the K transporters HAK5 and AKT1 (Rubio et al, 2008). We are currently unsure if reduced Mg in tsc10a is related to the changes in suberin observed in this mutant, since leaf Mg is unchanged in esb1 (Baxter et al, 2009).…”
Section: Discussionmentioning
confidence: 97%
“…Avoidance of the high concentration of NH 4 + in the Murashige and Skoog medium routinely used for Arabidopsis growth was important to prevent inhibition of K + uptake at low external K + concentrations (Spalding et al, 1999;Rubio et al, 2008). As recently described by Bassil et al (2011b), plants of the nhx1-1 nhx2-1 genotype were smaller than the wild-type and single mutant plants when grown in soil under standard growth conditions and in hydroponic culture in LAK medium (see Supplemental Figure 2 online).…”
Section: Functional Redundancy Of Nhx1 and Nhx2mentioning
confidence: 98%
“…Decreases in cytosolic K + content are thought to be required for induction and development of high-affinity K + uptake in Arabidopsis (Rubio et al, 2008). Three-week-old plants of Col-0 and mutant lines L2 and L14 growing in LAK hydroponic medium with 1 mM K + where starved in K + -free medium for 3 d and then assayed for ion uptake rates by roots using rubidium (Rb + ) at low (100 mM) concentration as a tracer for K + .…”
Section: Cytosolic K + Activitymentioning
confidence: 99%